Comparison of BES and other methods to estimate the parameter measurement of the distribution Whipple with two parameters using simulation - Zeina Moeen Mohammed Hussein (Iraqi Journal for Administrative Sciences, 2025)
This paper is concerned with problem of comparing different estimators of the scale parameter of two parameters Weibull distribution where is ( ( shape parameter and is scale parameter and then comparing the efficiency of the estimators which are maximum likelihood and minimax estimator with (quadratic loss function) and (modified linear exponential loss functions) the comparison was done using simulation procedure with different sample size and values of parameters ,on the bases of simulation experiment we conclude that minimax method with quadratic loss function was the best method at all sample size and values of parameters.